Spring birds - Dinsmore, James J.et al (1978)
Field report titled "spring birds," submitted by James J. Dinsmore. Some of the sightings were made by students of an ornithology class at Iowa State University. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring, 1978. Epson - sheet feed/flatbed